On an “unfathomable essential power”. On literatura from Heidegger - Moreno Tirado, Guillermo (Revista de Filosofía, 2023)
This paper interprets a short passage by Heidegger on the difference between literature and poetry and, especially, on the “unfathomable essential power” of literature. We will argue what the phenomenological features of this “power” of literature that distinguishes it from poetry, showing the internal problematicity of such a distinction. In order to foreground the meaning of this “unfathomable essential power” of literature, a brief reading of Don Quixote’s El curioso impertinente will be made. The conclusion is that the “unfathomable” power of literature lies in its ambivalence to be a means of homologation and resistance to that same homologation.